2023
DOI: 10.1186/s12891-023-06988-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of greater trochanteric bone density and three-dimensional morphology on perioperative greater trochanteric fracture following total hip arthroplasty via an anterolateral approach

Daisuke Inoue,
Tamon Kabata,
Yoshitomo Kajino
et al.

Abstract: Background Perioperative greater trochanteric fracture following total hip arthroplasty (THA) using the anterolateral approach is a recognized perioperative complication. There was no previous study to determine the relationship between bone mineral density (BMD) and three-dimensional greater trochanter morphology for perioperative greater trochanter fractures. The purpose of this study is to identify the influence of greater trochanteric bone density and three-dimensional morphology on periope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Templating methods have evolved in response to changes in the medical environment, although the key concept of templating as rehearsing the entire surgery has not changed. Templating methods can be broadly divided into (1) acetate templating on analog hardcopy, (2) acetate templating on digital images, and (3) digital templating on digital images, which can be further subdivided into 2D and 3D templating [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Templating methods have evolved in response to changes in the medical environment, although the key concept of templating as rehearsing the entire surgery has not changed. Templating methods can be broadly divided into (1) acetate templating on analog hardcopy, (2) acetate templating on digital images, and (3) digital templating on digital images, which can be further subdivided into 2D and 3D templating [5,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on decreases in bone density around an artificial joint, particularly after total hip arthroplasty (THA), have been widely seen. Inoue et al reported that the decrease in preoperative bone density is related to fractures of the greater trochanter during the perioperative period [17]. Additionally, Liu et al reported that the female patients older than 50 years lost significantly more bone density than the male patients [18].…”
Section: Introductionmentioning
confidence: 99%